Competency Model to Implement Smart Factory for Operator Level in Cosmetic Manufacturer (Case Study: PT XYZ) - Niken Noor Triastuti Murty Vijaya; Achmad Fajar Hendarman (Journal of International Conference Proceedings (JICP), 2019)
Manifestation on Smart Factory and Industry 4.0 is listed as one of PT XYZ strategic plans for the next five years. To fit that condition, company should define the competency model for operator level to work in the future manufacture. The first step was to define the framework of competency model to accommodate the needs of users. The second step was defining the competency model content by reviewing job, task, and competency needed by operator to perform the job. Author found that there are four technical competency and four non-technical competencies that are related to Smart Factory. The list were then arranged to illustrate the interrelation between competencies (Base and Pillar Competency Model) and in the form of Competency Matrix Mapping Model.